15 minutes environment : punctuate architecture - 216524 Mohd. Rizal Mohd. Rosly; Hamdan Ahmad, supervisor; Fakulti Alam Bina (2008)
Project Paper (Sarjana Muda (Senibina)) - Universiti Teknologi Malaysia, 2008